Geopolítica del desarrollo comunitario : reflexiones para trabajo social (2008)
ABSTRACT: The expansion of community development since the 1950s as an strategy to integrate populations considered to be in a marginal situation to industrial development, represented for the Social Service of the time, today the Social Work profession, the birth of one of the classical methods of intervention, the community one. The decline in importance of community development in the subsequent decades to the 1970s, has generated questioning about the place that community development had in the social matter, or its equalization with what is currently known as local development. This paper revises the international geopolitical framework within which community development took place as a concept and as a methodology, and its political insertion in the development, understood as Western modern progress. From this analysis, Social Workers are invited to reflect about the community perspective and power that underlies the encounter between communities and professional.